The Boldface Illusion: A New Visual Assimilation. (March 2013) - Fujimoto, Kiyoshi
This article introduces a new visual illusion. A thick line induces boldface appearance to adjacent letters or geometric figures. This boldface illusion suggests that visual features assimilate in terms of thickness.